SOCIAL AND HUMANITARIAN ASPECTS OF BUSINESS DIGITALIZATION - M. E. Kudryavtseva; L. M. Semyonova (Дискурс, 2018)
Business digitalization associated with the use of artificial intelligence algorithms, along with the emerging great opportunities in many areas of the national economy, is a far-reaching change with a number of negative consequences of a social and humanitarian nature. In terms of employment of population, it results in the disappearance of a number of traditional occupations, although it stimulates the growth of self-employment. In terms of education, digitalization poses a threat to culture as a tendency to narrow specialization. In terms of business communication, it triggers the growth of hoaxes in cyberspace. Solving these problems requires an integrated approach, involving joint efforts in the fields of employment of the population, higher education, and information and communication technologies.